2021
DOI: 10.1007/s40544-021-0512-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of the bio-tribology of medical devices

Abstract: Numerous medical devices have been applied for the treatment or alleviation of various diseases. Tribological issues widely exist in those medical devices and play vital roles in determining their performance and service life. In this review, the bio-tribological issues involved in commonly used medical devices are identified, including artificial joints, fracture fixation devices, skin-related devices, dental restoration devices, cardiovascular devices, and surgical instruments. The current understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 186 publications
(183 reference statements)
0
9
0
Order By: Relevance
“…Charnley's metal-on-polyethylene (MoP) total hip replacement (THR) is widely regarded as the gold standard for end-stage arthritis treatment. Further improvements include modular designs, consisting of (taper/trunnion) interface, which is convenient for surgeons when treating a wide range of patients [1]. However, due to the cyclic loading, fretting-corrosion at the taper/trunnion may result in adverse local tissue reactions (ALTRs) [2], leading to pseudotumours and THR failure.…”
Section: Introductionmentioning
confidence: 99%
“…Charnley's metal-on-polyethylene (MoP) total hip replacement (THR) is widely regarded as the gold standard for end-stage arthritis treatment. Further improvements include modular designs, consisting of (taper/trunnion) interface, which is convenient for surgeons when treating a wide range of patients [1]. However, due to the cyclic loading, fretting-corrosion at the taper/trunnion may result in adverse local tissue reactions (ALTRs) [2], leading to pseudotumours and THR failure.…”
Section: Introductionmentioning
confidence: 99%
“…This present study suggests that CCF-PEEK transfer films could be utilised to alter interfacial shear in practical applications, e.g. high-speed dry cutting [25] and artificial joints [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that the tribological properties are essential to the performance of implants in the human body. [ 8 ] The wear of articulating surfaces of artificial joints and generated wear debris, implant induced stress shielding are the main reasons for the failure of joint replacement. [ 9,10 ] Despite efforts paid to the improvement, the anti‐wear properties and bioactivities of such traditional biomaterials are still far from enough.…”
Section: Introductionmentioning
confidence: 99%